The Effectiveness of Information Services with the Jigsaw Cooperative Learning Model to Improve the Understanding of Discipline Learning of the Student - Arip Martua Hasibuan; Riska Ahmad; Yarmis Syukur (Universitas Negeri Padang, 2019)
The less understanding of the discipline learning by the student causes students to violate the rules and regulations that have been set in the school environment. This problem occurs because students are not aware of the meaning of the discipline learning, so it takes effort to improve students' understanding of the discipline learning. The understanding of learning discipline of the student is not seen in terms of attendance at school, taking lessons in class, managing time, school rules and free time. One of the efforts that made in improving student understanding is by the information service of the Jigsaw Cooperative Learning model. This study aimed to test the effectiveness of information services with the Jigsaw Cooperative Learning model to improve students' understanding of the discipline learning. This research used quantitative methods. The type of research was a Quasi Experiment with the design of The One Group Pretest-Posttest (without using a control group). The population of this study were Dian Andalas Padang High School students and the sample was selected using the Purposive Sampling technique. The instrument of the research was using a Likert Scale model (a questionnaire about the understanding of student learning discipline), the data were analyzed with the Wilcoxon Signed Ranks Test with the help of SPSS version 20. The results showed that the average score of pretest 123 and posttest 160. Based on the results of this study, it was concluded that the service information with the Jigsaw Cooperative Learning model is effective for increasing understanding of student learning discipline.